Endogenous hormone levels in explants and in embryogenic and non-embryogenic cultures of carrot - Jiménez García, Víctor (2001)
Carrot (Daucus carota L. F1 hybrid Starca) excised hypocotyls were cultured on Murashige and Skoog medium with and without 2,4‐dichlorophenoxy acetic acid (2,4‐D) to determine the effect of this plant growth regulator on their further development and their endogenous hormone levels. Culture in the absence of 2,4‐D stimulated root development at one end of the hypocotyl segments and increased the endogenous levels of free indole‐3‐acetic acid (IAA), zeatin/zeatin riboside and N6(Δ2‐isopentenyl) adenine/N6(Δ2‐isopentenyl) adenosine, as determined by radio‐immunoassay. On the other hand, the presence of 2,4‐D in the culture medium promoted callus induction and proliferation, together with abscisic acid (ABA) accumulation, in the hypocotyl segments during the first weeks of culture. When the callus segments generated in the hypocotyl sections cultured in the presence of 2,4‐D were cultivated further, the development of two callus types was observed, one composed of preglobular and globular embryos and the other translucent, watery and lacking any sign of organisation. The embryos of the first type germinated when callus segments were transferred to regeneration conditions, while no change was observed when the second type was induced to regenerate. Higher levels of free IAA and ABA were obtained in the embryogenic calli when compared to the non‐embryogenic, while no differences were observed among callus types in the other hormones evaluated. The possible role of the different plant hormones during induction of somatic embryogenesis is discussed.